Styrene radical cations for chemical ionization mass spectrometry analyses of monoterpene hydrocarbons - Spesyvyi, Anatolii; Španěl, Patrik; Sovová, Kristýna (Rapid communications in mass spectrometry, 2019)
RATIONALE: Monoterpene hydrocarbons play an important role in the formation of secondary aerosol particles and in atmospheric chemistry. Thus, there is a demand to measure their individual concentrations in situ in real time. Currently, only the total concentration of monoterpenes C10 H16 can be determined by chemical ionization mass spectrometry techniques using reagent ions H3 O+ , NO+ and (C6 H6 )n +• without gas chromatographic separation. METHODS: The styrene cation C8 H8 +• was investigated as a reagent for chemical ionization of monoterpenes. The modified selected ion flow drift tube, SIFDT, technique was used to characterize the differences in product ion distributions between α-phellandrene, α-pinene, γ-terpinene, β-pinene, ocimene, sabinene, 3-carene, (R)-limonene, camphene and myrcene. RESULTS: The monoterpene molecular cation C10 H16 +• is the main product (about 90%) for all isomers except (R)-limonene and camphene with an efficient channel of C8 H8 +• C10 H16 adduct formation and γ-terpinene with unexpectedly significant product ions at m/z 134 and 135 corresponding to losses of H2 and H. CONCLUSIONS: Utilization of the styrene cation for the ionization of monoterpenes is beneficial due to the very low fragmentation of the product ions. Specific association product ions for camphene and (R)-limonene and fragment product ions for γ-terpinene allow them to be distinguished from other isomers that produce mostly the molecular cation.